VILLAGE FINANCIAL MANAGEMENT (CHANGES APBDesa AND IMPLEMENTATION) IN THE TIME OF THE COVID-19 PANDEMIC - baihaqi baihaqi (UNIB Press, 2022)
This study aims to describe how the process of changing the Village Revenue and Expenditure Budget (APBDesa-P) is carried out, and how the implementation of its activities relates to socio-economic handling due to the Covid-19 outbreak in village financial management. With the issuance of PERPU Number 1 of 2020 concerning State Financial Policy and Financial System Stability for Handling the Corona Virus Disease (Covid-19) Pandemic, the government reallocated the budget starting from the APBN to APBDesa. This research use desciptive qualitative approach. The research data are in the form of secondary data (documents related to the research theme), primary data (interviews with informants, namely village financial managers, sub-district governments, and district governments) in the Rejang Lebong Regency area. Data analysis used the Miles and Huberman model.The results of the study prove that the process of preparing planning and budget documents (RPJMDesa, RKPDesa, and APBDesa) carried out by the Village government has followed the applicable rules and regulations. The initial stage is the formation of the RPJMDesa, RKPDesa, and APBDesa drafting teams by the Village Head, and then the team will work in accordance with the rules and regulations until the 2020 RPJMDesa, SKPDesa and APBDesa are stipulated. the existence of various rules and policies issued relating to the implementation of the activity program for the Village Cash Intensive Work (PKTD), and the Covid-19 Response Village. Furthermore, the Perbup regarding the Covid-19 Responsive Village and Village Cash Intensive Work to be a guideline for the village government. Activities in the Village are focused on carrying out PKTD activity programs, the essence of which is that Village Funds are used in a pattern through self-managed management, as well as the utilization of natural resources, appropriate technology, innovation and human resources. The Village Government does not make changes to the Village Budget related to the existence of these programs and activities. The government makes adjustments to the implementation of the Village Budget.